Strategi Ekonomi Pertahanan dalam Mengatasi Tantangan Sosial Ekonomi dan Meningkatkan Ketahanan Nasional - Muhammad Fikri Abdillah; Lukman Yudho Prakoso; Suwito Suwito (CV. AFDIFAL MAJU BERKAH, 2025)
This research aims to analyse the relationship between socio-economic inequality, measured by the Gini Ratio, and national security, as well as develop a defence economic strategy to overcome socio-economic challenges and increase national resilience in order to realise the vision of a golden Indonesia in 2045. The method used is qualitative with review techniques from literature, which involves in-depth analysis of various relevant sources of information such as scientific journals, books, government reports, and other official documents. The research results show that increasing socio-economic inequality, reflected in the increase in the Gini Ratio in urban areas since 2019, has the potential to threaten national stability. This inequality can trigger social discontent and violence, which ultimately impacts national security. Therefore, effective economic policies are needed to reduce income inequality, improve economic opportunities, and ensure a fair distribution of resources. These policies include implementing progressive taxes and social welfare programmes, increasing access to education and health services, and encouraging inclusive economic growth that benefits all levels of society. By addressing socio-economic inequality and strengthening national security, Indonesia can achieve its vision of a Golden Indonesia 2045 and ensure sustainable development for future generations.